This Mine is Mine! How Minerals Fuel Conflicts in Africa - Berman, Nicolas; Couttenier, Mathieu; Rohner, Dominic; Thoenig, Mathias (The American economic review, 2017)
We combine georeferenced data on mining extraction of 14 minerals with information on conflict events at spatial resolution of 0.5° × 0.5° for all of Africa between 1997 and 2010. Exploiting exogenous variations in world prices, we find a positive impact of mining on conflict at the local level. Quantitatively, our estimates suggest that the historical rise in mineral prices (commodity super-cycle) might explain up to one-fourth of the average level of violence across African countries over the period. We then document how a fighting group's control of a mining area contributes to escalation from local to global violence. Finally, we analyze the impact of corporate practices and transparency initiatives in the mining industry.